High performance computing for large graphs of internet applications using GPU - Uddin, Jia; Oyekanlu, Emmanuuel; Kim, Cheol-Hong; Kim, Jong-Myon (© 2014 Science and Engineering Research Support Society, 2016)
This article was published in the International Journal of Multimedia and Ubiquitous Engineering [© 2014 SERSC] and the definite version is available at :http://dx.doi.org/10.14257/ijmue.2014.9.3.25 The Journal's website is at:http://hgpu.org/?p=11807